Binary Effect of Palm Oil Fuel Ash and Eggshell Waste Powder on Heat of Hydration for Mortar - Jamellodin, Zalipah; Arif Jamal, Mohamad; Nor Azhar, Norazreen; A. Majid, Masni; Salleh, Norhafizah; Azlina Abdul Hamid, Noor; Hani Adnan, Suraya (International Journal of Engineering and Technology, 2018)
The effects of mortar containing palm oil fuel ash and eggshell waste powder on heat of hydration was investigated. This study covers the basic properties like the chemical composition of raw materials and the hydration temperature for binary mortar. Malaysia is one of the worldâ€™s largest palm oil producers. Palm oil fuel ash (POFA) is a product of the combustion of palm oil waste which is not used and usually disposed of in landfills. The use of eggs in the food industry also generate waste egg shells that can be transform into powder namely eggshell waste powder (ESP). The development in construction technology has contributed to research in producing various methods and materials that provide advantages in the construction field. One of the technologies is to investigate the effectiveness of OPC replacement with appropriate waste materials. In this research, POFA and ESP was used as ingredients to replace a proportion of OPC in the mortar thereby reducing the use of OPC. POFA used in this study were in forms of ground POFA (GPOFA) and unground POFA (UPOFA). GPOFA and ESP are ground to achieve a similar size as OPC while UPOFA was used in its original size. The total percentages replacement of POFA and OPC was 20% by weight with the different level replacements of 4%, 8%, 12%, 16% and 20%. The design of mortar mix proportion made up of three groups, A, B and C. Group A is the control mortar that is OPC only. Group B is the mortar that contains OPC, POFA and ESP. Meanwhile, a third group C, consisting of a mixture of OPC, GPOFA and ESP. The mix proportion used for hydration temperature determination was chosen from the previous study which identified the strength of mortar compression. The optimum compressive strength of each group is chosen to obtain the mortar hydration temperature. For determination of mortar hydration temperature, plywood with size 300 mm x 300 mm x 450 mm cube was used as the exterior mold. It was packed with 76 mm thick polystyrene acting as the insulator. Polyvinyl chloride (PVC) pipe with diameter of 150 mm and a height of 300 mm is used to fill the mortar mix. A thermocouple (Type K) was inserted into the center of each box and was connected to a data logger system. Temperature rises due to heat of hydration in all mixes were recorded for 5 days. The results revealed that the replacement of OPC with binary materials is beneficial, particularly for mass mortar where thermal cracking due to excessive heat rise is of great concern.Â